Rapid Maxillary Expansion for Obstructive Sleep Apnea among children - Systematic Review and Meta-analysis - Sarah Ahmed Bahammam (Sleep Science, 2020)
A systematic review and meta-analysis is conducted for children with obstructive sleep apnea (OSA) treated with rapid maxillary expansion (RME). The study systematically and independently reviewed extracted articles from 2009 to 2019. The quality evaluation and selection of these studies was based on the high quality of NICE criteria. EMBASE, Scopus and other five databases were used to extract international publications. The findings indicated that the apnea-hypopnea index was enhanced after rapid maxillary expansion among children with OSA. It revealed that apnea hypopnea index enhances to 73% in children with obstructive sleep apnea after ≤ three years follow-up, while it was 77% in children with obstructive sleep apnea after > 3 years. The articles included in this meta-analysis reported differential outcomes based on different inclusion or exclusion criteria and diverse patient populations. Critical evaluation of previous literature suggests diagnosing the disorder at an early stage for reducing the adverse health outcomes and formulating an appropriate treatment plan.